2009
DOI: 10.1212/01.wnl.0000338626.93425.74
|View full text |Cite
|
Sign up to set email alerts
|

Georges Marinesco and the early research in neuropathology

Abstract: Marinesco was a prolific researcher in the field of neuropathology, especially neurodegeneration but also in clinical neurology. He is now considered the founder of the modern Romanian school of neurology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 12 publications
1
22
0
Order By: Relevance
“…The city of Bucharest was chosen because of its long history in neurological research and scientific tradition [2]. The congress was dedicated to Sir Gheorghe Marinescu (1863-1936) who established a chair of Clinical Neurology at the University of Bucharest, in Colentina Hospital in 1897 [3,4]. He worked there for 41 years and is regarded as the founder of the Romanian School of Neurology [3].…”
mentioning
confidence: 99%
“…The city of Bucharest was chosen because of its long history in neurological research and scientific tradition [2]. The congress was dedicated to Sir Gheorghe Marinescu (1863-1936) who established a chair of Clinical Neurology at the University of Bucharest, in Colentina Hospital in 1897 [3,4]. He worked there for 41 years and is regarded as the founder of the Romanian School of Neurology [3].…”
mentioning
confidence: 99%
“…In the mid to late 19th century, clinical-pathologic studies of persons with dementia demonstrated atrophy and a reduction of brain weight, which were thought to result from ‘hardening of the arteries’ [1]. Senile plaques were first identified by Blocq and Marinesco in 1892 but these investigators did not make the link to dementia [2]. However, in separate papers in 1906, Alzheimer and Fischer each reported that senile plaques and neurofibrillary tangles were associated with dementia [3, 4].…”
mentioning
confidence: 99%
“…The French neuropathologists Paul Oscar Blocq (1860–1896) and Gheorghe Marinesco (1863–1938) in 1892 first described the presence of ‘sclerotic plaques of neuroglia’, a name which Emil Redlich changed to ‘miliary sclerosis’ or ‘drusen’ in the aging human brain neocortex [19]. The term ‘ amyloid’ originated from an early mistaken identification by the German neuroanatomist Rudolf Virchow (1821–1902) of a neural and CNS substance resembling starch (‘ amylum’ in Latin) – since it has been subsequently acknowledged that amyloids are, in fact, deposits of ‘ proteinaceous albumoid ’ material [116].…”
Section: Historical – the Drusen (Amyloid ‘Esenile’ Plaques) Of Admentioning
confidence: 99%